2018
DOI: 10.1002/smll.201801352
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical CdS Nanorod@SnO2 Nanobowl Arrays for Efficient and Stable Photoelectrochemical Hydrogen Generation

Abstract: An efficient photoanode based on CdS nanorod@SnO nanobowl (CdS NR@SnO NB) arrays is designed and fabricated by the preparation of SnO nanobowl arrays via nanosphere lithography followed by hydrothermal growth of CdS nanorods on the inner surface of the SnO nanobowls. A photoelectrochemical (PEC) device constructed by using this hierarchical CdS NR@SnO NB photoanode presents significantly enhanced performance with a photocurrent density of 3.8 mA cm at 1.23 V versus a reversible hydrogen electrode (RHE) under A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 74 publications
1
41
0
Order By: Relevance
“…All these structural and compositional advantages of TiO 2 NR@NB arrays lead to enhanced PEC performance with a photocurrent density of 1.24 mA cm −2 at 1.23 V versus RHE under 100 mW cm −2 AM 1.5G irradiation (Figure F–H). To achieve better performance, materials responsive to visible light should be incorporated in the similar frame‐like structure . A nanosphere lithography method combined with hydrothermal growth was used to fabricate CdS NR@SnO 2 NB arrays, which exhibits a photocurrent density of about 3.8 mA cm −2 at similar conditions.…”
Section: Heterostructured Photocatalysts With Open Hollow Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…All these structural and compositional advantages of TiO 2 NR@NB arrays lead to enhanced PEC performance with a photocurrent density of 1.24 mA cm −2 at 1.23 V versus RHE under 100 mW cm −2 AM 1.5G irradiation (Figure F–H). To achieve better performance, materials responsive to visible light should be incorporated in the similar frame‐like structure . A nanosphere lithography method combined with hydrothermal growth was used to fabricate CdS NR@SnO 2 NB arrays, which exhibits a photocurrent density of about 3.8 mA cm −2 at similar conditions.…”
Section: Heterostructured Photocatalysts With Open Hollow Structuresmentioning
confidence: 99%
“…To achieve better performance, materials responsive to visible light should be incorporated in the similar frame-like structure. [97] A nanosphere lithography method combined with hydrothermal growth was used to fabricate CdS NR@SnO 2 NB arrays, which exhibits a photocurrent density of about 3.8 mA cm −2 at similar conditions.…”
Section: Frame-like Heterostructured Photocatalystsmentioning
confidence: 99%
“…[1][2] The rational design and fabrication of suitable photoanode materials are crucial for achieving efficient PEC water splitting system. [10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination. [6][7][8][9] The PEC application of CdS has been intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination. [27][28][29][30] For example, complex CdS architec-tures, such as three-dimensional (3D), [10,11] inverse opal arrays [12][13][14] and branched nanoarrays [15][16][17] have been fabricated. [18][19][20][21][22] The sulfide/sulfite ions as hole scavengers are always necessary for stable operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation